Exploring The Psychological Dimensions And Conflicts Of The Main Character In The Movie The Greatest Showman - Kanda Dwisatya Ardana; Luh Putu Laksminy (International Journal of Linguistics and Discourse Analytics, 2026)
Understanding the psychological dimensions and internal conflicts of film characters is important in examining how emotions, motivations, and behaviors shape character development. While film character analysis is well established, a gap remains between psychological theory and its applied use in analyzing character transformation (specify this gap more clearly). This study examines the psychological dimensions and conflicts of Phineas Taylor Barnum in The Greatest Showman (2017). Using a qualitative analytical approach, this research applies psychological theory and conflict theory to analyze Barnum’s internal drives and emotional struggles. Data were collected through close viewing of the film, using documentation and note-taking techniques, that reflect Barnum’s psychological traits and conflicts. The scenes were analyzed by classifying them according to five psychological dimensions (list or briefly define) and two types of conflict, internal and external. The findings show that Barnum’s personal development is influenced by ambition, emotional needs, and the desire for social acceptance (this is expected—add a more specific insight). These psychological aspects create narrative tensions that drive his transformation throughout the narrative. The study concludes that Barnum’s character is shaped by dynamic psychological negotiation and conflict resolution, providing insight into character construction in fil. This research contributes to discussions of psychological analysis in cinematic narratives.